Analysis of Critical Thinking Skills (CTS) as a ‘Survival Kit’ in 21st Century World - India, AbdulMumini (International Journal of Psychosocial Rehabilitation, 2020)
Critical thinking is fast becoming most important skills needed for surviving the challenges of the digital age. The era of Information and Communication Technology (ICT) challenges the world with its rocket- like speed of too many information and developments. Recent studies have identified skills needed for withstanding the challenges; Collaboration, Communication, Critical and Creative thinking skills (4cs), though additional one is added by other researchers to include Caring. The twenty first century requires individuals to have key competencies that are important for the achievement of all SDGs, as well as educational approaches and tools for the implementation of these competencies. The methodology adopted for this research involves critically analysing related theories (such as Critical Theory) and researches. It identified the key variables based on the subject area, identified the independent and dependent variables and the connections were presented using a flow chart. Elements of critical thinking as contain in Paul-elder Critical thinking framework were considered with brief analysis on Islamic theoretical framework and blooms theory of critical thinking. A conceptual framework for critical thinking for teaching Islamic studies was produced